Economic value and environmental impact of Saddang River sand mining, Pinrang Regency, South Sulawesi, Indonesia - Arsyad, Arsyad; Rukmana, Didi; Salman, Darmawan; Alimuddin, Ilham; Arifin, Muh. Aris; Jamaluddin, Jamaluddin; Hamzah, Hamzah; Nurdirman, Eris; Ihsan, Muh.; Bauna, Ruslan; Reno, Reno; Tinta, Yulis (Journal of Degraded and Mining Lands Management, 2024)
This research aimed to determine the social, economic, and environmental impact of Saddang River sand mining on local communities and the Pinrang district government. Primary data collection used field surveys to obtain supporting data on economic aspects consisting of production capacity, costs, selling price of sand at the miner level and market price at the consumer level, number of grains, and various other economic values such as indirect value and indirect use value. The primary data collection method uses a total sampling of 80 miners operating in the research area. Consumer data uses a field survey method with 8 hours of observation per day. Saddang River sand mining provides great socio-economic value and environmental impact, directly or indirectly. This significant socio-economic value and impact, if not accompanied by good management, can result in over-exploitation, which impacts the physical and ecological damage of the Saddang River. On the other hand, the high rate of sedimentation from upstream of the Saddang River results in shallowing, so sand mining activities help normalize the Saddang River. Therefore, to continue providing economic benefits and the Saddang River to avoid physical and ecological damage due to mining activities, sustainable management of Saddang River sand mining is needed.